Selective adsorption of plant cysteine peptidases onto TiO2 - Llerena Suster, Carlos Rafael (2009)
A crude extract rich in plant cysteine peptidases was obtained from the latex of the fruits of Araujia hortorum, a South American climbing plant. The highly concentrated extract was immobilized onto titanium dioxide to produce biocatalysts through a simple adsorption procedure. Absorbance measurement at 280 nm and Bradford's method for protein quantification revealed that the protein content of the crude extract was selectively adsorbed onto the titanium dioxide surface at a very high rate. In 5 min of contact with the support all protein present in the crude extract was selectively withdrawn from the solution, leading to an immobilized biocatalyst with a high protein concentration. Caseinolytic assays indicated that, except for the catalyst obtained with the highest crude amount contacted with the support, all the proteolytic activity present in the crude extract was adsorbed onto TiO2. The amidasic activity of the immobilized catalysts (Ah/TiO2) was tested in the hydrolysis of a synthetic chromogenic substrate (PFLNA) showing partial deactivation with respect to the native enzyme. In amidasic activity assays the ionic strength of the buffer medium showed to be a key feature to consider in order to avoid protease desorption from the support, indicating the importance of electrostatic interactions between the enzymes and TiO2. Reuse of the produced biocatalysts with PFLNA as substrate revealed that after five successive uses Ah/TiO2 retained more than 20% of its initial activity. © 2009 Elsevier B.V. All rights reserved.